2009
DOI: 10.1016/j.biopsycho.2008.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Fear-conditioned respiration and its association to cardiac reactivity

Abstract: This study aimed to investigate ventilatory correlates of conditioned fear responses. Respiratory, end-tidal carbon dioxide pressure (PetCO 2 ) and heart rate changes were studied in a differential fear conditioning paradigm. Forty-two participants viewed pictures of faces. One picture (CS+) was followed by a human scream (US) during the acquisition phase, but not in a subsequent extinction phase. Conditioning of PetCO 2 (decrease), respiratory cycle time (decrease) and inspiratory duty time (increase) was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…SBP increased for auditory and tactile stimuli, but showed a strong decline for olfactory stimuli. Autonomic responses are highly dependent on context and relevant action tendencies (Van Diest et al, 2009) and the different the patterns observed may indicate different action tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…SBP increased for auditory and tactile stimuli, but showed a strong decline for olfactory stimuli. Autonomic responses are highly dependent on context and relevant action tendencies (Van Diest et al, 2009) and the different the patterns observed may indicate different action tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…There were two unpleasant noises. One was a 2 s, 80-db female scream, which was selected based on unpleasantness ratings of young adults (M ¼ 1.21; high aversion) (Van Diest, Bradley, Guerra, Van den Bergh, & Lang, 2009). The other was a 0.2 s, 80 db of white noise, of low aversion (no normative information available).…”
Section: Apparatusmentioning
confidence: 99%
“…Partial pressure of end-tidal CO 2 (P et CO 2 ) measurement is the only deterministic indicator of hyperventilation (10) and the gold standard for the non-invasive assessment of hyperventilation. It is measured as the partial pressure of CO 2 at the end of each expiration.…”
Section: Introductionmentioning
confidence: 99%